PERANAN SEKRETARIAT DALAM MEMAKSIMALKAN FUNGSI PELAYANAN ADMINISTRASI PERKANTORAN DI BIDANG SEKRETARIAT DINAS PERDAGANGAN PERINDUSTRIAN DAN KOPERASI UKM KABUPATEN SIKKA - Wihelmina Beatris; Imanuel Wellem; Paulus Juru (Jurnal Projemen UNIPA, 2026)
This research aimed to analyze the role of the secretariat in maximizing office administrative service funtions within the secretariat division of the departement of trade, industry, and cooperatives and SMEs of sikka regency. This research used a qualitative approach with data colletion techniques including interviews, observations, and document studies. The key informant in this research was the head of the secretariat division. Data analysis was conducted interactively through the stages of data colletion, data reduction, data presentation, and conclusion drawing. The result showed that the secretriat has carried out office administrative functions systematically and in a structured manner, covering routine, technical, analytical, interpersonal, and managerial functions. The management of correspondence and archives has been implemented following the established procedures, although it remained largely manual and faced challenges such as delays in letter numbering and limited supporting facilities. The utilization of information technology through the srikandi application has proven to improve work efficiency, however, it still requires enhanced human resource competencies and stronger technological infrastructure support. In terms of analysis and reporting, the secretariat played an important role in preparing administrativereports and providing accurate data to support managerial decision-making. Furthermore, the secretariat also held a strategic role in fostering coordination, communication, and harmonious working relationships within the organization.